The athlete biological passport: challenges and possibilities. Issue 2 (3rd April 2019) - Devriendt, Thijs; Chokoshvili, Davit; Borry, Pascal
ABSTRACT: The Athlete Biological Passport (ABP) relies on the longitudinal monitoring of blood and urine variables impacted by doping use. Since the introduction of the Haematological Module of ABP, it has quickly become a pivotal tool in anti-doping testing. Nevertheless, the ABP has brought new ethical challenges to the anti-doping community. Of particular importance is whether ABP data should be accessible by athletes or not. Such data disclosure could damage the integrity of the anti-doping system as athletes may monitor effectively the results of their doping habits. Moreover, there might be other ramifications resulting from data disclosure. Another issue is how incidental findings within ABP data, such as data indicating a potential underlying pathology, should be reported. In this regard, the inclusion of additional data in the ABP, such as variables involved in hormonal axes or -omics data, could bring new challenges. Crucial to the disclosure of incidental findings is the manner in which they should be disclosed and to whom. Some genotyping information may be useful for anti-doping authorities although this brings difficulties such as the return of information in case variants are also linked to medical conditions, the potential that such information fuels prejudices against particular groups, the restrictions of genetic information in occupational health and insurance and the proportionality of the collection of such data. In view of the obstacles the aforementioned issues might bring for the anti-doping community, it is evident that discussions should take place proactively to ensure robust and sound policy in the future.